Aplikasi mordan tanin pada pewarnaan kain batik katun menggunakan warna alam tingi (Ceriops tagal) - Dwi Wiji Lestari; Vivin Atika; Yudi Satria; Aprilia Fitriani; Tri Susanto (Jurnal Rekayasa Proses, 2020)
The aim of the study was to evaluate the performance of tannin mordant from Psidium guajava leaves, Peltophorum pterocarpum bark, and Coffea arabica leaves in cotton batik dyeing using tingi bark (Ceriops tagal). This research was conducted by initial quantitative analysis of each extract to measure the quantity of tannin using UV-Vis spectrophotometry with tannic acid as a standard solution. The next process was a fabric pre-mordanting using each mordant extract, batik process, coloring with tingi bark extract, and post-mordanting using each alum solution and guava leaves extract. The dyed batik fabric was tested toward its color intensity and durability/fastness properties. From the quantitative analysis, guava leaves extract contains the biggest tannin content compared with jambal bark and coffee leaves extract, which is 1151.5 μg/mL. The dyed sample from combination of Guava leaves extract pre-mordanting with alum post-mordanting provided the best color intensity of 15.52. While all variables had an equal good value for washing fastness. It can be concluded that all material had potential as natural mordant for cotton batik dyeing with natural dye, but with consideration of using metal mordant for combination to get better results in terms of both color intensity and fastness properties.